Inclusive Political Rhetoric and Identity Construction: An Aristotelian Analysis of Ganjar Pranowo’s Speech in the Context of Indonesian Electoral Discourse - Sari, Lusi Komala; Asrywan, Panji; Onwuagboke, Bede Blaise Chukwunyere (Actual Insight, 2025)
Amid the growing polarization of identity politics ahead of Indonesia’s general election, political communication plays a central role in shaping public opinion and constructing collective identity. While much of contemporary political practice tends to exploit exclusive symbols based on ethnicity, religion, and social class, alternative approaches through inclusive rhetoric remain underexplored. This study aims to analyze how Ganjar Pranowo, through his political speech, constructs an inclusive narrative in response to the discourse of identity politics. The study employs Aristotelian rhetorical theory (logos, ethos, and pathos) as the primary framework to examine the persuasive strategies embedded in the speech. A qualitative approach with rhetorical discourse analysis is used. Data were drawn from transcripts of Ganjar Pranowo’s public speeches delivered during the national political campaign. The research instruments included a classification of rhetorical categories and thematic content analysis to interpret the strategic function of each rhetorical element. The findings reveal that Ganjar’s speech integrates rational argumentation, moral credibility, and emotional resonance in a balanced manner. He deploys narratives of social justice, equitable access, and recognition of marginalized groups as strategies to frame national identity inclusively. These results confirm that political rhetoric functions not only as a tool of electoral persuasion but also as a constitutive medium that reconstructs collective identity and challenges political exclusivism.